Sub-Saharan Africa. Identity, Tradition, Memory - Anna Bruna Menghini (Festival dell'Architettura Magazine, 2023)
Aside from economic and social questions, the African Continent is also now confronting the delicate question of cultural identity. The historical process marked by the phases of colonisation/decolonisation/globalisation-global colonisation, has had, and continues to have, a profound influence on African architectural culture, in which it is possible to recognise diverse attitudes. Urban culture is generating a complex and articulated reflection by artists and architects tackling the effects of contemporary globalisation, as well as the contradictory legacy of colonialism and stereotypes linked to African identity. Rural contexts, instead, are witnessing a renewed emergence of an approach that considers the needs of dwelling expressed by local communities, re-elaborating architectural culture and traditional construction.